50 games for going green physical activities that teach healthy environmental concepts - Scaini, Carol; Evans, Carolyn 1957- (Human Kinetics, 2012)
A resource for teachers and youth leaders wishing to educate children about the importance of caring for the environment through the medium of fun physical activities. It is filled with simple games and activities that can not only engage children in physical activity, but also inspire them to appreciate and take care of the earth